(untitled) (Journal Of Educational and Psychological Researches, 2010)
It has became necessary helping the children to developing same of educational values which can be drawn from daily situations which the live. Especially the childhood stage is the basic building of value individual content since its establishment the societies take care of learning children and take care of them. Through their institutes which depended on, in this function. Therefore the importance of this, research is coming from the importance of this age stage and from importance and necessity of children aguirement the educational values and its development to them, and the importance this research coming from depending on guidance program with new content and it is (al bum of pictures) from his family there the research has importance appears through the importance of that, the individual have the educational values which make him a builder person in his society, and the childhood is the base of this individual ,so that this research aims to; 1-knowing the daily situations that the child of kindergarten lives which drawn farm same of educational values. 2-knowing the educational values, which drawn from daily situations when the child of kindergarten lives. 3-knowing the effect of guidance programmer in developing the educational values which drawn frame daily situation whom the child of kindergarten lives. And to achieve the aim this research the researcher built measurement tool the drawn educational values from daily situations and it has displayed that there are five daily situations drawn from their educational values and the most important of them, values are(clean lines and believing in Allah) and also displayed that there are effect of guidance programmer in album of pictures in developing same educational values which drawn from same of daily situations ,the researcher has put same recommendations and she suggests applied this programmer on another sample of children like the first primary school.